Engineering the semiconducting CdS nanostructures by N-doped rGO for enhancing the adsorption sites: Promising electrocatalyst for hydrogen evolution reaction. (29th April 2022) - Murugan, R.; Rebekah, A.; Allen, J.A.; Preethi, M.; Viswanathan, C.; Ponpandian, N.
Abstract: The development of non-noble electrocatalysts for hydrogen production from water is of immense interest as it is clean and eco-friendly. The present work explores the electrocatalytic performance of morphologically varied CdS NPs synthesized using different sulphur source and ionic liquids via hydrothermal treatment, in catalyzing hydrogen evolution reaction (HER). The hierarchical flower shaped morphology denoted as CdS–N3 outperformed other prepared electrocatalysts with a Tafel slope value of 118 mV dec −1 and a low overpotential 344 mV @ a current density of 10 mA/cm 2 . However, the outperformed CdS–N3 catalyst when blended with N doped rGO, it showed a superior activity with a low overpotential of 201 mV at 10 mA/cm 2 . The catalyst disclosed a small Tafel slope of 70 mV dec −1 corroborating that the catalyst contains more electroactive sites and oxygen vacancy voids for the adsorption-desorption of charge carriers generated from the heteroatom doping. The CdS/N-rGO catalyst also revealed a higher TOF value of 5.18 × 10 −3 s −1, which further proves that catalyst is more efficient in releasing H2 molecules and this findings affirms that CdS/N-rGO catalyst can be an efficient candidate for initiating HER kinetics with endurable stability in acidic medium for high purity hydrogen production. Graphical abstract: Image 1 Highlights: Morphologically tuned CdS nanostructures and CdS/N-rGO composite was developed. The electrocatalytic performance towards HER was investigated. Catalyst exhibiting hierarchical flower shows better electrocatalytic performance. CdS/N-rGO composite outperformed due to more active sites and oxygen vacancies. Exhibited low overpotential of 201 mV @ 10 mA/cm 2 by following Volmer step.